Magnesium ions regulate the Warburg effect to promote the differentiation of enteric neural crest cells into neurons - Qiongqian Xu; Xixi He; Yaru Mou; Dong Sun; Xintao Zhang; Jichang Han; Xiaoyang Liu; Xingjian Liu; Xue Ren; Dongming Wang; Jian Wang; Chuncan Ma; et al. (Stem Cell Research & Therapy)
Abstract Background Understanding how enteric neural crest cells (ENCCs) differentiate into neurons is crucial for neurogenesis therapy and gastrointestinal disease research. This study explores how magnesium ions regulate the glycolytic pathway to enhance ENCCs differentiation into neurons. Materials and methods We used polymerase chain reaction, western blot, immunofluorescence, and multielectrode array techniques to assess magnesium ions' impact on ENCCs differentiation. Non-targeted metabolomic sequencing, cellular acidification rate, oxygen consumption, and western blot analyzed sugar metabolism changes. D-glucose-13C6 isotope tracing identified key glucose flux changes. Surface plasmon resonance was used to detect the binding affinity of magnesium ions with key glycolysis genes. The elastic modulus of the hydrogel was measured using a universal testing machine, while pore size and porosity were assessed with scanning electron microscopy. Swelling ratios were determined using gravimetric analysis. In vivo, ENCCs in hydrogels were transplanted into renal capsule and subcutaneously, and magnesium ions' effects on ENCCs differentiation were evaluated. Results Magnesium ions increased glycolysis levels during ENCCs differentiation into neurons, along with significant upregulation of neuronal markers β-Tubulin and ubiquitin C-terminal hydrolase L1, and enhanced functional neuronal properties. D-glucose-13C6 tracing results showed increased carbon flux in the glycolytic pathway after magnesium supplementation. The binding affinity of magnesium ions with the glycolytic key enzyme 6-phosphofructo-2-kinase/fructose-2,6-biphosphatase 3 was found to be 1.08 μM. Inhibiting glycolysis suppressed ENCCs differentiation into neurons, emphasizing its crucial role. The double-cross-linked hydrogel gelatin methacryloyl—alginate (gelMA—ALMA), cross-linked with magnesium ions, showed promise in enhancing ENCCs differentiation in vivo without causing systemic hypermagnesemia. Conclusion Magnesium ions promote ENCCs differentiation into neurons by activating the Warburg effect. The GelMA-ALMA hydrogel serves as an effective localized magnesium delivery system, supporting neuronal differentiation in vivo. Graphical abstract Magnesium ions target PFKFB3, enhancing glucose flux towards G3P and subsequent lactate production, while also promoting ENCCs differentiation into neurons by facilitating NAD+ generation, suppressing ROS, and maintaining mitochondrial homeostasis. Mg: Mg2+, Glu: glucose, LA: lactic acid. Ref to the creation software of the picture.